Gender parity in peer assessment of team software development projects - Tom Crick (Computing Education Practice 2022, 2022)
Development projects in which small teams of learners develop software/digital artefacts are common features of computing-related degree programmes. Within these team projects, it can be problematic ensuring students are fairly recognised and rewarded for the contribution they make to the collective team effort and outputs. Peer assessment is a commonly used approach to promote fairness and due recognition. Maintaining parity within assessment processes is also a critical aspect of fairness. This paper presents the processes employed for the operation of one such team project at a UK higher education institution, using the Team-Q rubric and analysing the impact of the (self-identified) gender of learner mark- ing and the learner being marked on the scores obtained. The results from this institutional sample (N=121) using the Team-Q metric offers evidence of gender parity in this context. This study also makes the case for continued vigilance to ensure Team-Q and other rubrics are used in a manner that supports gender parity in computing.